POLA TABUHAN MUSIK TERBANGAN DI KABUPATEN OGAN ILIR SUMATERA SELATAN - Rifki, Dian; Yelli, Nofroza (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
This research aims at elaborating the percussion pattern of Terbangan music in Tanjung Batu sub-district Ogan Ilir district. The observation was conducted by using observation technique, interview, and documentation on one of the performances of Terbangan music in Ogan Ilir district Sumatera Selatan. The research method used was a qualitative method so it's obtained research result in which Terbangan music is art that uses the musical instruments of Terbangan and gong. Terbangan comes from Arabian country played by hitting it using hand palm. This musical instrument of Terbangan is made of Leban wood that has a round form with 30 cm diameter and 10 cm height. The surface of Terbangan uses x-ray plastic. This musical instrument belongs to the kind of membranophone musical instrument, and it means that the sound produced comes from beating on the membrane. The other musical instrument as accompaniment is gong made of brass with a bulge in the middle of the gong. The pattern of percussion in the art consists of three parts namely the percussion pattern of initial rhythm, the percussion pattern of kincat rhythm, and the percussion pattern of yahum rhythm.